1999
DOI: 10.1038/sj.bjc.6690061
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of specific genes in MCF-7 and the ICI 182780-resistant cell line MCF-7/182R-6

Abstract: SummaryTo elucidate the mechanisms involved in anti-oestrogen resistance, two human breast cancer cell lines MCF-7 and the ICI 182780-resistant cell line, MCF-7/182 R -6, have been compared with regard to oestrogen receptor (ER) expression, ER function, ER regulation, growth requirements and differentially expressed gene products. MCF-7/182 R -6 cells express a reduced level of ER protein. The ER protein is functional with respect to binding of oestradiol and the anti-oestrogens tamoxifen, 4-hydroxy-tamoxifen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
4
32
2
Order By: Relevance
“…MCF-7 cells are totally oestrogen dependent, MCF-7/TAM R -1 are slightly oestrogen independent and MCF-7/182 R -6 are almost completely oestrogen independent for growth in vitro and in vivo (Lykkesfeldt et al, 1994;Jensen et al, 1999;Larsen et al, 1999). We have shown here for the first time, that it is favourable, with respect to treatment with EB1089, that the anti-oestrogen-resistant cells have progressed into a less hormone-dependent state, with a reduced expression of oestrogen-regulated genes e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF-7 cells are totally oestrogen dependent, MCF-7/TAM R -1 are slightly oestrogen independent and MCF-7/182 R -6 are almost completely oestrogen independent for growth in vitro and in vivo (Lykkesfeldt et al, 1994;Jensen et al, 1999;Larsen et al, 1999). We have shown here for the first time, that it is favourable, with respect to treatment with EB1089, that the anti-oestrogen-resistant cells have progressed into a less hormone-dependent state, with a reduced expression of oestrogen-regulated genes e.g.…”
Section: Discussionmentioning
confidence: 99%
“…EB1089 has also been shown to inhibit tumour growth of a newly established ICI 182 780 resistant MCF-7 subline in nude mice (Nolan et al, 1998). In this study, we have used two well characterized anti-oestrogen resistant cell lines, MCF-7/TAM R -1 and MCF-7/182 R -6 (Lykkesfeldt and Briand, 1986;Lykkesfeldt and Sørensen, 1992;Wiseman et al, 1993;Lykkesfeldt et al, 1994Lykkesfeldt et al, , 1995Larsen et al, 1997Larsen et al, , 1999Madsen et al, 1997;Jensen et al, 1999), and observed that these resistant cell lines responded to treatment with EB1089. In fact, they were more sensitive than the parent MCF-7 cells.…”
mentioning
confidence: 84%
“…Previously, we have found high levels of ERα mRNA in MCF-7 cells by Northern analysis , Jensen et al 1999), and the ERα protein level has been measured as 400-600 fmol/mg cytosol protein in MCF-7 cells (Lykkesfeldt et al 1994. By Western analysis a specific protein band has been detected at 65 kDa with ERα-recognizing antibodies ).…”
Section: Discussionmentioning
confidence: 99%
“…However, upon long term removal of estrogen from the culture medium, the cells gradually adapt, developing an ability to grow without estrogen until they can eventually grow at the same rate as they had done previously only in the presence of estrogen (38 -40). Similar adaptive processes enable the cells to escape from growth inhibition imposed by the anti-estrogens tamoxifen (41) and ICI 182,780 (42) or by retinoic acid (43). The molecular basis for this growth adaptation remains unknown, but recent work has shown that development of estrogen hypersensitivity resulting from up-regulation of ER and increased estrogen-regulated gene expression may be involved (44).…”
mentioning
confidence: 99%